Peran Mediasi Faktor Demografi pada Pengaruh Financial Attitude, Locus of Control dan Financial Knowledge Terhadap Personal Financial Management Behavior: Study Kasus pada Pegawai Tetap Universitas Muhammadiyah Sumatera Utara - Olivia, Dhea; Lestari, Sri Puji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Research aims to testing the influence of financial attitudes, Locus of Control, financial knowledge on the behavior of personal financial management through the role of mediation factors of demographics focusing on age and working period of respondents studied. The population of this research is the remaining employee of the University of Muhammadiyah North Sumatra, which amounted to about 300. SPRESSING SCHAMED ABDER 75 respondents with Slovin formula to know the number of respondents is the employee remains University of Muhammadiyah North Sumatra. Methods of data collection wears a questionnaire. Data analysis using SmartPLS 4.1.0.0. The results of research, financial knowledge has a positive effect on demographic factors, financial knowledge has a positive effect on personal financial management behavior, and Locus of Control has a positive effect on behavior of personal financial management. Private personnel behavior is very important in life. Each individual has a certain level of financial knowledge to help apply the behavior of personal financial management. In addition, each individual is endowed with intelligence and level of personal financial knowledge that enables them to perform activities in financial management. Financial knowledge greatly has an effect on personal financial management behavior. The better financial knowledge, the better also financial management. A person's decision in financial management is also inseparable from the role of demographic factors of age and work. Age also affects the decision in the behavior of personal financial management. The higher the age and effort of individuals will be better as well as in the management of personal finances and can be more focus in the short-term and long-term personal management of the applicable appearance in the form of behavior